Genesis of Progressive T‐Cell Deficiency Owing to a Single Missense Mutation in the Common Gamma Chain Gene - Goldman, A. S.; Palkowetz, K. H.; Rudloff, H. E.; Dallas, D. V.; Schmalstieg, F. C. (Scandinavian journal of immunology, 2001)
Patients with a moderate X‐linked combined immunodeficiency (XCID) owing to a single missense mutation in the common gamma chain (γc) gene (L→Q271) were found to have a progressive T‐cell deficiency. Blood T cells from four older subjects with XCIDL→Q271 were studied to ascertain the basis of that progression. Few CD4+ T cells displayed the phenotype (CD45RA+ CD62L+) or deletion circles from T‐cell receptor (TCR) Vβ‐gene rearrangements found in recent thymic emigrants. These deficiencies were more severe in older males with XCIDL→Q271. Relative frequencies of fresh CD4+ and CD8+ T cells that bound annexin V, an early indicator of programmed cell death, or propidium iodide, an indicator of cell necrosis, were greater in XCIDL→Q271 T cells than in normal fresh T cells. The binding of annexin V and propidium iodide to XCIDL→Q271 T cells increased marginally after stimulation with anti‐CD3, but binding by fresh or stimulated XCIDL→Q271 T cells exceeded that found in normal stimulated T cells. Also, telomeres from XCIDL→Q271 CD4+ T cells were shortened in these patients compared to normal young adults. It therefore appears that the thymus is dysfunctional and that mature T cells are not effectively rescued from apoptosis or replication senescence via γc‐mediated pathways in XCIDL→Q271.